Heaven and Earth - Stone, Oliver (Warners Bros. Production, 2001)
From three-time Academy award - winning filmmaker Oliver Stone - Whose Platoon took you to the Vietnam battlefront and whose Born on the Fourth of July took you to the American homefront - comes an acclaimed movie about the fight to survive on both fronts. Tommy Lee Jones and Joan Chen" turn in award-caliber performances" (Peter Travers, Rolling Stone) in the powerful story of a man who fought, a woman who endures...and love caught up in the explosive wartime upheaval of a land and a people caught between Heaven and Earth.